2002
DOI: 10.1159/000067486
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Techniques for Enteral Nutrition: Standards and Innovations

Abstract: Enteral nutrition has been increasingly used in clinical practice during the past decades. Today, nasogastric, nasoenteric, and transcutaneous gastric or enteral feeding tubes are well established as a routine endoscopic intervention. After clinical introduction of percutaneous endoscopic gastrostomy (PEG) in 1980, the sutureless ‘pull’ PEG has become a widespread endoscopic technique for transcutaneous gastric long-term nutrition. Multiple new techniques have been introduced since then, and today even long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 50 publications
0
33
0
4
Order By: Relevance
“…Borgaonkar and Dormann (16,17) found that the evaluation of QOL is quite difficult due to the health status of the patients. The physician's view is crucial, but the patient's interpretation regarding his/her condition can be important.…”
Section: Discussionmentioning
confidence: 99%
“…Borgaonkar and Dormann (16,17) found that the evaluation of QOL is quite difficult due to the health status of the patients. The physician's view is crucial, but the patient's interpretation regarding his/her condition can be important.…”
Section: Discussionmentioning
confidence: 99%
“…The types of tubes have different indications, advantages and complications. Specifi c details of insertion have been described before [38] .…”
Section: Enteral Nutritionmentioning
confidence: 99%
“…In gastric tumors, nasogastric feeding is often ineffective and the risk of aspiration pneumonia is high in patients with delayed gastric emptying [37] . The indication for nasoenteral feeding should primarily be given in cases with malignant outlet stenoses [38,39] . In these patients, two or three lumen tubes should be preferred because they increase the tolerance of enteral feeding by simultaneous gastric decompression [39] .…”
Section: Tube Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, conservative medical management was instituted. A week later, percutaneous endoscopic gastrostomy was performed with the Funada-style loop fixture II (Create Medic, Yokohama, Japan) to avoid collapse of the stomach wall (4,5). Laceration of the lower esophagus had almost healed.…”
mentioning
confidence: 99%